Penerapan Metode Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) pada Sistem Pendukung Keputusan untuk Menentukan Kualitas Beras Terbaik Berbasis Web - Zulfahmi, Zulfahmi (Journal Digital Technology Trend, 2024)
This study aims to develop a web-based decision support system using the Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) method to determine the best rice quality in Pidie Regency, assisting farmers in selecting high-quality rice for consumption or seeds. Primary data were collected through interviews and observations with farmers and agricultural experts, identifying five evaluation criteria: grain size, moisture content, color, aroma, and protein content. The system was built using PHP, HTML/CSS, JavaScript, and MySQL, with the MOORA process involving decision matrix creation, normalization, criteria weighting, and alternative ranking. Testing revealed a system accuracy of 87.5% and user satisfaction of 4.2 out of 5, with Rice A achieving the highest rank (optimization value of 0.892). The system offers a practical solution with a user-friendly interface, reducing subjectivity in rice quality assessment, though limited to 10 alternatives and excluding market price factors. This research contributes to Pidie’s farmers by enhancing decision-making efficiency and paving the way for web-based agricultural technology development.